Staffing practices in Lebowa - Mmola, Stephen Matome (My University, 1982)
Refer to the document
Thesis (M. A. (Administration)) -- University of the North, 1982
Keywords: Staffing; Manpower; Employee management; Civil service -- South Africa -- Lebowa; Lebowa (South Africa) -- Officials and employees; Personnel management; Employees -- Recruiting